The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/mec.14899
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary melting pots and reproductive isolation: A ring‐shaped diversification of an odorous frog (Odorrana margaratea) around the Sichuan Basin

Abstract: Quaternary climatic oscillations and geography are of primary importance in shaping intraspecific genetic diversity. We examined the diversification patterns and inferred processes for the green odorous frog (Odorrana margaretae) of western China. Species distribution modelling showed that the species has a continuous circular distribution around the Sichuan Basin while the basin itself is largely uninhabitable. Population genetic and phylogenetic analyses revealed that the species has a ring‐shaped divergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 69 publications
(113 reference statements)
10
42
0
Order By: Relevance
“…Bashan, Dalou and Qinling is patchier and lower in elevation. The discovery of this corridor supports the possibility of ring-like distributions among montane species around the Sichuan Basin (see Qiao et al, 2018), which is a precondition for the existence of ring species (Monahan, Pereira, & Wake, 2012).…”
Section: Allopatric Diversification Shaped By the Mountain And Draisupporting
confidence: 62%
“…Bashan, Dalou and Qinling is patchier and lower in elevation. The discovery of this corridor supports the possibility of ring-like distributions among montane species around the Sichuan Basin (see Qiao et al, 2018), which is a precondition for the existence of ring species (Monahan, Pereira, & Wake, 2012).…”
Section: Allopatric Diversification Shaped By the Mountain And Draisupporting
confidence: 62%
“…This supports the hypothesis that the development of the East Asian Monsoon notably impacted intraspecific divergence and population dynamics. Further investigations using the ring distance of the IBD patterns suggested that extant P. zhennan populations displayed a ring‐shaped distribution around the Sichuan Basin, supporting the hypothesis that the Sichuan basin may have served as biogeographic barrier (Qiao et al, 2018), facilitating ring diversification.…”
Section: Discussionmentioning
confidence: 52%
“…The molecular results suggest a Late Pliocene to early Pleistocene origin for the West clade endemic to the hotspot edge, in which the area around sites 21–24 and 26 has consistently been modeled to be suitable for L. boringii in the LIG, LGM, MH, and current periods. Western marginal refugia and areas of long-term persistence within or overlapping with this hotspot edge have been proposed for some mountain amphibian [ 37 , 79 ], mammal [ 47 ], insect [ 50 ], and flowering plant species [ 38 , 39 , 52 , 53 , 80 – 82 ]. Additionally, gene flows from the east via mountains along the edges of the Sichuan Basin have recently been reported for different species [ 37 , 48 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Western marginal refugia and areas of long-term persistence within or overlapping with this hotspot edge have been proposed for some mountain amphibian [37,79], mammal [47], insect [50], and flowering plant species [38,39,52,53,[80][81][82]. Additionally, gene flows from the east via mountains along the edges of the Sichuan Basin have recently been reported for different species [37,48,83]. Together with these findings, our results imply that the preservation of eastern taxa, facilitated by the continuous mountain topography surrounding the basin, contributes significantly to regional biodiversity.…”
Section: Spatial Heterogeneity Of the Factors That Influence High Biomentioning
confidence: 99%
See 1 more Smart Citation